THE ORGANS OF THE REFORMED DIOCESE FROM ERDŐVIDÉK - EXAMINATION PAPER ABOUT THE HISTORY OF THE ORGANS - PART I - - István Zoltán KISGYÖRGY (Studia Universitatis Babeş-Bolyai. Musica)
When choosing the theme of my research, I was guided by the desire to get to know and investigate the organ, as a musical instrument, and by the affection and love for my homeland. I thought that I would choose a theme and a searching area, that has been infolded only in the slightest extent, and which constitutes an important piece of the history of Erdővidék and of the reformed diocese from Erdővidék. Many researchers surveyed the organs of Transylvania[1], among others Dávid István published his results too. With my work I would like to complete this research of great dimensions, especially the part referring to the reformed churches from Erdővidék, and to correct the occurent false informations, and confirm them with authentic data.